2021
DOI: 10.1007/s10495-021-01666-0
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Mechanistic Characterization of a Select Modulator of AhR-regulated Transcription (SMAhRT) with Anti-cancer Effects

Abstract: Background: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor and a member of the bHLH/PAS (basic Helix-Loop-Helix/Per-Arnt-Sim) family of proteins. The AhR was cloned and characterized for its role in mediating the toxicity of dioxins. Subsequent research has identi ed AhR's role in the suppression of cancer cell growth. We hypothesized that that the AhR is a molecular target for therapeutic interventions, and that activation of the AhR by select AhR modulators in cancer cells cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…None of these compounds mirrored the BMP phenotype of 1a in any of the assays, excluding adenosine-associated effectors as responsible targets. The same was true for the very recently reported activity of 1a on the aryl hydrocarbon receptor, which we could exclude as a BMP-relevant target compared to the selective AhR activator FICZ (Figure S6A–D).…”
Section: Resultssupporting
confidence: 77%
“…None of these compounds mirrored the BMP phenotype of 1a in any of the assays, excluding adenosine-associated effectors as responsible targets. The same was true for the very recently reported activity of 1a on the aryl hydrocarbon receptor, which we could exclude as a BMP-relevant target compared to the selective AhR activator FICZ (Figure S6A–D).…”
Section: Resultssupporting
confidence: 77%
“…A long list of synthetic [1,[7][8][9][10][11][12][13], endogenous [14,15] and dietary molecules [16] have been identified that bind to AhR, in addition to ligands produced by commensal microbiota [17]. There is significant interest in developing AhR-targeted therapeutics for multiple diseases, particularly autoimmune disorders [18][19][20] and cancer [3,[8][9][10]21,22]. The feasibility of therapeutically targeting AhR is supported by the absence of overt toxicity in vivo when select highaffinity ligands are administered [11,19,20].…”
mentioning
confidence: 99%
“…affinity and metabolic fate) and the biological context. A long list of synthetic [1,[7][8][9][10][11][12][13], endogenous [14,15] and dietary molecules [16] have been identified that bind to AhR, in addition to ligands produced by commensal microbiota [17]. There is significant interest in developing AhR-targeted therapeutics for multiple diseases, particularly autoimmune disorders [18][19][20] and cancer [3,[8][9][10]21,22].…”
mentioning
confidence: 99%
“…Conversely, FICZ promotes the differentiation of inflammatory TH17 cells in certain contexts ( 28 , 69 ). AhR ligand-dependent conformational states leading to the recruitment of specific transcriptional coregulators and chromatin remodelers, or tissue-specific expression of coregulators, have been reported as mechanisms of AhR ligand-mediated immune cell polarization ( 70 75 ). Additionally, the concentration of AhR ligands within the microenvironment, and the subsequent duration of AhR activation, have been shown to elicit opposing T cell subsets ( 76 ).…”
Section: Discussionmentioning
confidence: 99%